Punch card data processing in haematology - Nelson, M. G. (1969)
A method of processing haematological laboratory data based on the IBM 870 system is described. As the cards are being punched with the identification particulars of the patient and source of the sample, a worksheet is automatically generated on which the tests are indicated. The results of the laboratory tests are recorded by the technician on the worksheet and reproduced on the punch cards which are subsequently used for the automatic printout of the results on self-adhesive preprinted labels. The resulting report is clear and legible and is transferred onto the request/report document. The data processing is carried out by clerk/typists who have been trained as punch card operators. The present workload of approximately 2,000 items of information obtained from some 170 samples per day is handled by one punch card operator in less than three hours. The punch cards are manipulated in a sorter for quality control purposes and are stored for subsequent retrieval of information.